MASYARAKAT MEMANDANG GRATIFIKASI DALAM TINDAK PIDANA KORUPSI. - Bethesda, Elisabeth (Jurnal Komunikasi Hukum (JKH), 2019)
Law that exist in communitydevelopsalongside the community itselfand is based on community awareness in order to avoidindividual and community interestsdisorders. Further, to make the law beneficialto the community, then the provisionsof law are adjusted to the living law. The agreed law contains precautions to avoid violation ofnorms or customs.Gratification as an immoral actin the Anti-Corruption Law; it even compares gratification withbribery. However, gratification must be eradicated although the community viewsit as a good norm and need to be preserved. Giving or receiving gifts among the giver and the recipient becomes a 'problem' when the act of giving and receiving is stated as an act of violatingthe criminal law.